Low-temperature Technologies - Morosuk, Tatiana; Sultan, Muhammad (IntechOpen, 2020)
Low-temperature technologies include the area of refrigeration and cryogenics. Since the beginning of theoretical developments and practical application, these technologies become a part of our life. Low temperatures have found application in almost all branches of industries as well as in households. These systems can be of very small capacity (few watts) up to hundreds of megawatts. In order to develop any of the technologies for successful practical application, very intensive theoretical and experimental research should be conducted. This book provides the reader with a comprehensive overview of the latest developments, perspectives, and feasibility of new low-temperature technologies and improvements of existing systems, equipment, and evaluation methods.